A new possible breeding site of Alosa fallax (Lacépède 1803) (Actinopterygii: Clupeiformes: Alosidae) on the Tyrrhenian coast of Central Italy - Vincenzo Ferri; Paolo Crescia; Christiana Soccini; Stefano Celletti (Natural History Sciences, 2024)
The River Mignone (Tarquinia, Viterbo, central Italy) is one of the best preserved watercourses in Lazio. Here, in April and May of the years 2020-2023, a conspicuous contingent of Alosa fallax (Lacépède 1803) was reported. The frenetic behaviour of the individuals observed, some of which showed swollen bellies and considerable size, suggested that this watercourse may represent a potential new breeding station for this threatened migratory euryhaline fish species. The correct recognition of the sex of A. fallax in the field, problematic during the breeding season, is crucial for understanding its population structure as indicators of possible reproduction. To this end, statistical analysis (Mann-Whitney U-test) of 20 morphometric measurements made on individuals captured and subsequently released revealed significant differences between the sexes for seven morphometric characters, confirming a sex ratio compatible with reproduction. However, the presence of a transverse dam with no fish ladder and the dispersion of biocides from farmland in the final stretch may represent a serious threat to effective reproduction.